Impact of Articulated Management Models on Educational Quality in Peru: A Systematic Review - Orozco, Mgs. Evert Peña; Castillo, Mgs. Juan Alberto Castillo; Córdova , Mgs. Milquiades Enrique Roña (Journal of Ecohumanism, 2024)
This study aimed to analyze the impact of articulated management models on improving educational quality and equity in Peru. Through a systematic review of the literature with a qualitative approach that applied the PRISMA methodology in the search in the databases: Scopus, SciELO, Redalyc, Dialnet, and the library of the César Vallejo University, various studies are identified that explore the characteristics, implementation and results of these models. The results showed that articulated management models have significant potential to improve the quality of teaching and learning, especially when the participation of the educational community is promoted and transformative leadership is available. However, challenges are identified such as lack of resources, resistance to change and the need for continuous teacher training. It is concluded that articulated management models represent a promising way to improve education in Peru, but their implementation requires a comprehensive approach and educational policies that support them.